Life history notes on Bicyclus dorothea Cramer (Nymphalidae: Satyrinae) in Cameroon - Dongmo, M.A.K.; Bonebrake, T.C.; Fomena, A.; Hanna, R. (2017)
Bicyclus d. dorothea (Cramer, 1779) is a widely distributed butterfly inhabiting much of the northern part of the tropical African rainforest. The biology of the species has not been well studied despite it being relatively common throughout its distribution. In this study, we report on the life history of B. d. dorothea following three years of research on the species in Cameroon. We describe the life cycle of the species and report on key life history aspects such as distribution, habitat, reproduction, and host plant relationships.